Analisis Semiotika Roland Barthes pada Lirik Lagu Album Untuk Dunia, Cinta, dan Kotornya Karya Nadin Amizah - Tri Wulandari; Ririn Rahayu; Masithah Mahsa (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This research aims to describe Roland Barthes' semiotic analysis on the lyrics of the song lyrics of Untuk Dunia, Cinta, dan Kotornya album by Nadin Amizah. This type of research is descriptive qualitative. The research data sources are 11 songs. The research data is in the form of words, sentences or stanzas. Research technique. The research technique uses listening and note-taking techniques. Based on the research results, it was found semiotic meaning, namely (1) denotation totaling 97 data; (2) connotation totaling 97 data; (3) myth totaling 36 data, in total, there are 230 data. System Roland Barthes meaning starts from the signifier and produces a signified from the 11 songs titles. Songwriters tend to use figurative language or poetic language or what is commonly called meaning that is not real so that it is difficult to understand. While the least data is myth because not all sentences in the eleven songs have a point of view regarding the ideology of society towards the interpretation of culture.